Exploring AI-Enabled Cloud Transformation Towards Digitalization Value in Accounting Firms - Sudawadee Intho; Daranee Uachanachit (Ital Publication, 2026)
This study examines how AI-enabled, cloud-based accounting platforms generate digitalization value within Thai accounting firms by identifying the internal mechanisms through which cloud capability and cloud user capability translate into economic outcomes. Using survey data from 360 cloud-using firms, we employed covariance-based structural equation modeling with maximum likelihood estimation and bias-corrected bootstrapping (5,000 resamples) to test direct and mediated pathways. The results show that the qualitative of accounting information produced by cloud systems strongly enhances digitalization value added (β = 0.49, p < 0.001) and promotes proactive work behavior (β = 0.59, p < 0.001). Proactive work behavior further contributes to digitalization value added (β = 0.30, p < 0.01). Cloud user capability improves information quality (β = 0.19, p < 0.05) and proactive behavior (β = 0.35, p < 0.01), while cloud attributes improve information quality (β = 0.10, p < 0.05). Mediation analysis confirms that value arises indirectly via the sequential chain from cloud capability to information quality and then to proactive behavior, indicating that technical readiness alone is insufficient without informational uplift and behavioral execution. Theoretically, we extend information-systems and capability-based perspectives by positioning qualitative accounting information and proactive work behavior as the conversion channels that render cloud technology economically meaningful. Practically, firms and regulators should shift emphasis from infrastructure deployment to managing information quality, building user capability, and institutionalizing proactive work routines within AI-enabled cloud settings so that cloud adoption yields measurable value.